Dance with me : ballroom dancing and the promise of instant intimacy - Ericksen, Julia A., 1941- (New York University Press, 2011)
Rumba music starts and a floor full of dancers alternate clinging to one another and turning away. Rumba is an erotic dance, and the mood is hot and heavy; the women bend and hyperextend their legs as they twist and turn around their partners. They slide their feet along the floor toes first, transferring their weight from leg to leg, and settling their hips after each move to produce the rolling hip action, which is particularly visible in this slow-paced dance. Amateur and professional ballroom dancers alike compete in a highly gendered display of intimacy, romance and sexual passion.